ANALISIS PENGELOLAAN SAMPAH DAN KETERSEDIAAN INFRASTRUKTUR TEMPAT PEMBUANGAN SEMENTARA (TPS) DI KOTA GORONTALO - Nurul Hikma Aulia; Marike Mahmud; Arfan Utiarahman (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Negeri Gorontalo, 2025)
Effective waste management remains a major challenge in urban areas, including Kota Selatan Subdistrict, Gorontalo City, which is experiencing an increase in waste volume due to population growth and economic activities. Infrastructure limitations, particularly in the availability of Temporary Disposal Sites (TPS), have resulted in waste accumulation and pose a risk of increased environmental pollution. This research aims to analyze the volume of waste generation, evaluate the existing conditions of TPS, ad assess the capacity of infrastructure in handling waste in Kota Selatan Subdistrict, Gorontalo City. This research employs a quantitative analysis method combined with field surveys focusing on waste volume and the availability of Temporary Disposal Site (TPS) infrastructure in Kota Selatan Subdistrict. Data collection involved direct observation, recording of waste volume generated, interviews with waste management officials, and sampling following the procedures established in SNI 19-3964-1994. The results indicate that the total volume of waste in Kota Selatan Subdistrict reaches 111,03 m3/day, with contributions from residential sources at 6,01% and non-residential sources at 93,99%. The availability of TPS infrastructure is highly limited, with only two (2) functioning container units out of the ideal requirement of approximately 19 units. The percentage of waste successfully transported reaches 82,95% of the total daily waste generation, leaving about 17,05% uncollected. Meanwhile, the waste transport frequency achievement in the research area stands at 82,64% of the targeted frequency.